The Cabinet of Ministers of Ukraine as a subject of legal relationships of legal responsibility in the pharmaceutical sphere - O. H. Aleksieiev (Aktualʹnì Pitannâ Farmacevtičnoï ì Medičnoï Nauki ta Praktiki)
The aim of work is research of legal status of central executive authorities as subjects of legal relations of legal responsibility arising in the pharmaceutical sphere of Ukraine from the standpoint of pharmaceutical law.